Observaciones excepcionales de especies de Gymnetis (Coleoptera. Cetoniidae) en colmenas de abejas meliferas (Hymenoptera: Apiidae) en Perú - Tejada, Graciano; Morón, Miguel Ángel (Instituto de Ecología, A.C., 2015)
During March, 2013 large numbers of specimens of Gymnetis pudibunda Burmeister and G. chevrolat Gory et Percheron were attracted to honey bee hives in localities of Virú and Lurín, Peru. Around 150-200 cetonid beetles were observed around each beehive, and some of them invaded honey reservoirs. Brief comments to explain the increase of cetonid populations are included.